Caracterización funcional en cáscara de coco para su aprovechamiento de economía circular en Bachillero, Tosagua - Cedeño Anchundia, Yandry Antonio (2024)
This research focused on the functional characterization of coconut shells to promote circular economy actions in the Bachillero parish of the Tosagua canton. An area of 7 hectares was studied where agricultural practices related to coconut cultivation generate a considerable environmental impact due to the accumulation of residues. The analysis determined that coconut shell has a high water absorption capacity, reaching up to 80% of its weight, with a retention of 78%. Through community surveys, it was revealed that 87% of the population is concerned about the negative effects of this waste, although 63% are unaware of the possible applications of the peel. However, 81% showed a willingness to use derivatives from the shell, reflecting an interest in taking advantage of this by-product in a sustainable way. The research underscores the importance of implementing technologies and techniques that allow coconut shells to be transformed into useful products, such as biodegradable materials, components for green building and agricultural substrates. This approach would not only contribute to reducing environmental impact, but could also generate new economic opportunities for the community, aligning with the principles of sustainable development and circular economy.